Winning Strategy of the Elected Village Head in the Tugumulyo Village Election, Ogan Komering Ilir Regency - Tarisa, Tarisa; Febriyanti, Doris; Amaliatulwalidain , Amaliatulwalidain (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the winning strategies of the elected village head in the 2019 Tugumulyo Village Head Election, focusing on the formulation and application of offensive and defensive strategies along with supporting factors for success. Methodology/approach: The research took place in Tugumulyo Village, Lempuing District, Ogan Komering Ilir Regency, South Sumatra, Indonesia. A qualitative descriptive method was applied through observation, open interviews, and documentation. Informants included the elected village head, campaign team, religious leaders, heads of hamlets, and community members. Data were analyzed thematically to identify the main factors influencing the outcome. Results/findings: The elected candidate, Sugianto, applied offensive strategies such as a clear vision and mission, an organized campaign team, religious facility support, and direct engagement with residents. Defensive strategies included cultural closeness with the majority Javanese community, active participation in social events, and maintaining personal relationships with voters. These efforts produced a victory with sixty point five percent of votes, winning thirty seven out of forty polling stations, with voter turnout reaching eighty three point forty eight percent. Conclusions: A well balanced mix of offensive and defensive strategies, supported by cultural alignment and strong community ties, can greatly increase the likelihood of winning local elections. Limitations: The study is limited to one case in a single village, which may affect broader applicability. Contribution: The study enriches local political strategy literature and offers practical insights for researchers, policymakers, and future candidates in rural elections.